Analytical allocation of new construction methods based on future residential demand to modify residential construction efficiency plan - Majid Paziki; Mahdi Ravanshadnia (مهندسی و مدیریت ساخت, 2018)
In these days having a suitable, affordable, and safe housing is one of the main concern of people around the world. This concern makes government and authorities try to find the best solution for it based on the new techniques, and modern research tools. In Iran, also, the housing market has been all the time important and considered as a important factor in developing.Housing comprehensive plan help us to have a good understanding from housing in the future. In this plan, goals in a five-years period for Iranian families will be stated. Unfortunately, [1] because of many economical, social and technical problems accessing to the predicted goals is difficult. This can be seen from the 2006 plan as well as 2014 plan, where none of them could apply for housing market.[2]In this study, new construction methods, their advantages and disadvantages and of course their effects in different areas will be analyzed, and using expert’s view a solution will be considered. This solution is based on the resources and limitations of areas and gives the best method for construction. In conclusion, the best way for any zones for improving housing efficiency in that area will be introduced to be supported and developed in order to provide affordable and cheap housing for low-income people [3-5].